2021
DOI: 10.1016/j.jsps.2021.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic monitoring of amiodarone and desethylamiodarone after surgical ablation of atrial fibrillation-evaluation of the relationship between clinical effect and the serum concentration

Abstract: Background Association between clinical effect and serum concentration of amiodarone (AMI) and its active metabolite desethylamidarone (DEA) in patients after surgical ablation (SA) of atrial fibrillation (AF) has not yet been studied. Aims We wanted to find a correlation between AMI and DEA serum concentration and maintaining sinus rhythm (SR) after SA of AF. Methods Sixty eight patients with AF who had undergone surgical ablation between 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Table 1 summarizes the characteristics of the 19 included articles. In the clinical setting, blood concentrations were used with the intention of performing dose adjustments (ie, TDM) in 5 studies, [9][10][11][12][13] although only 3 studies reported a change in amiodarone treatment. [10][11][12] From these 3 published studies, only the case report by Munnink et al used TDM to modify the amiodarone dose during rifampicin treatment, whereas the 2 case reports by Kim et al and Sato et al discontinued amiodarone treatment due to side effects and toxicity.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Table 1 summarizes the characteristics of the 19 included articles. In the clinical setting, blood concentrations were used with the intention of performing dose adjustments (ie, TDM) in 5 studies, [9][10][11][12][13] although only 3 studies reported a change in amiodarone treatment. [10][11][12] From these 3 published studies, only the case report by Munnink et al used TDM to modify the amiodarone dose during rifampicin treatment, whereas the 2 case reports by Kim et al and Sato et al discontinued amiodarone treatment due to side effects and toxicity.…”
Section: Resultsmentioning
confidence: 99%
“…3 For dosage modifications, 5 clinical studies used blood amiodarone concentration measurements. 9–13 Amiodarone concentration measurements were used to adjust amiodarone medication 1–12 months after surgical ablation in a prospective observational study of 68 patients with atrial fibrillation. 9 There were no statistical differences in doses or concentrations of amiodarone or MDEA between individuals with maintained sinus rhythm and those with tachyarrhythmias, and both sinus rhythm and tachycardia were detected within the complete concentration range (0.11–2.5 mcg/mL).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations